1994
DOI: 10.1159/000097087
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropeptide Alpha-Melanocyte-Stimulating Hormone Inhibits Experimental Arthritis in Rats

Abstract: Α-Melanocyte-stimulating hormone (Α-MSH) modulates inflammatory processes in models of acute inflammation and in models of sepsis/septic shock/ adult respiratory-distress syndrome (ARDS). Because this neuropeptide inhibits actions of cytokines and other mediators of inflammation that are also believed to underlie aspects of chronic inflammation, tests were performed to compare the effects of repeated administration of the peptide with those of prednisolone and saline on the development of adjuvant arthritis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 0 publications
5
59
0
2
Order By: Relevance
“…The peptide is safe when given in large and consistent doses to animals or humans. 26,27,29 However, it is very unstable in vivo and therapeutic use would require daily administration. 26,27,29 Researchers have been developing aMSH analogs, such as [Cys4, Cys10]-aMSH 33 and [Nle4,D-Phe7]-aMSH 34 , to increase activity and stability relative to native aMSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide is safe when given in large and consistent doses to animals or humans. 26,27,29 However, it is very unstable in vivo and therapeutic use would require daily administration. 26,27,29 Researchers have been developing aMSH analogs, such as [Cys4, Cys10]-aMSH 33 and [Nle4,D-Phe7]-aMSH 34 , to increase activity and stability relative to native aMSH.…”
Section: Discussionmentioning
confidence: 99%
“…25 The ability of aMSH to inhibit NF-kB translocation makes it an interesting target for therapeutic intervention. In fact, aMSH and its analogs have shown therapeutic activity in many animal disease models [11][12][13][14] such as inflammatory bowel disease, 26 arthritis 29 and hepatitis. 27 However, the inherent instability of the peptide does not make it suitable for use as a therapeutic agent in humans.…”
mentioning
confidence: 99%
“…To date five MCRs have been identified and they are all positively coupled to adenylate cyclase, signaling via protein kinase with agonism at these receptors leading to increases in intracellular cAMP [11]. Melanocortin peptides have long been reported to possess antiinflammatory effects in many experimental models of acute [12][13][14] and chronic inflammation, including inflammatory bowel disease [15], joint arthritis [16,17] and activation and consequent cytokine synthesis within the first few hours of treatment [20,21] and at later time points (>8h) induce the anti-inflammatory protein hemeoxygenase 1 [22] and IL-10 [24]. Only one study has so far addressed the role of α-MSH in modulating eosinophil accumulation levels in a murine model of allergic airway disease [19]: α-MSH treatment of allergic mice led to a significant reduction in inflammation and this protective effect was associated with augmented IL-10 production.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…αMSH treatment has been shown to ameliorate several experimental models of inflammatory diseases such as systemic inflammatory response,19 autoimmune encephalomyelitis,20 and systemic lupus erythematosus 21. Similarly, αMSH administration decreases the clinical and histological signs of experimental arthritis 22. We have recently reported that peripheral αMSH administration to arthritic rats has anti‐inflammatory and anti‐cachectic effects, since it ameliorates arthritis‐induced anorexia and muscle proteolysis 23…”
Section: Introductionmentioning
confidence: 99%